Women Education in the Muslim World: Some Hard Truths - Hassan, Maniul; Sengupta, Maumita (Journal of Innovation in Education and Social Research, 2026)
Women Education has always been an important aspect of every civilisation, scholars have famously said “The hand that rocks the cradle rules the world”. India has been known for it’s woman scholars since it’s ancient period, but contemporary India has it’s share of problems in this regard too. The study focuses on the data provided on various parameters for higher education of Muslim women in Murshidabad district of West Bengal. The data are presented alongwith suggested solutions according to educational experts of Murshidabad.